AN ANALYSIS OF THE POLITENESS USED IN PODCAST “FRIENDS OF MERRY RIANA” - Melati (Fakultas Ilmu Budaya and LPPM Universitas Sebelas April, 2023)
This study aims to identify and classify the politeness principles used and contained in Merry Rianna's podcast with Rudy Salim and Cinta Laura, and also to analyze the function of the politeness principles used and contained in Merry Rianna's podcast with Rudy Salim and Cinta Laura. The method used in this research is descriptive qualitative. The data collection technique used is the observation and note-taking technique. The object under study was a conversation on the podcast